An experimental study on enhancement of cutting tool properties by tool hardening and hard coating method. (2021) - Nithiyapathi, C.; Kannan, C. Ramesh; Balaji, R.Suresh; V.Preethi,
Abstract: The cutting apparatus is a prime significant instrument required in metal expulsion activities for delivering the parts. It produces part as well as keeps up the dimensional exactnesses, geometrical tolerances and wanted surface finish of the machined part. In order to meet all the specific parameters like wear, surface finish, and hardness, etc., there are various cutting-edge technologies are evolving now a days for the betterment in achieving quality. In this paper, experimental study is carried out to identify high reliable tools with hard coated cutting tools (mix and addition of cutting material and hard coatings) where is necessary to regularize the coating and hardening procedures to test new tools at normal working conditions. Here the machining performance of cutting tool in machining SS140 material, uncoated, stellite coated, solidified hardened tools were inspected and their wear, handling time and resultant machined piece surface completion were analyzed.